PENGARUH REKRUTMEN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. SAMUDRA OCEANEERING BATAM - Giska Anggia Putri; Susi Hendriani; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine how the variables influence Recruitment and Training either simultaneously or partially on employee performance in PT Samudra Oceaneering Batam.In this study there were 51 samples of the total number of employees located in Batam PT Samudra Oceaneering totaling 103 people. The analysis used in this study is the method of multiple linear regression analysis. By using SPSS version 18.From the test results of multiple linear regression analysis, known simultaneous test results (Test F) that the variables simultaneously Recruitment and Training significant effect on performance. From the results of multiple linear regression analysis of the results showed that the variable recruitment of more dominant effect on the variable to variable Performance Training. The results of the partial test (Test T) note that the variable Recruitment and Training Influential significantly to performance, and training variables also have a significant effect on performanceKeywords: Recruitment, Training and Employee Performance